Re‐Examining Advances in Occupational Licensing Research: Issues and Policy Implications - Bryson, Alex; Kleiner, Morris M. (British journal of industrial relations, 2019)
Much has changed in the realms of occupational licensing since BJIR last ran a special issue on the subject in 2010. The number of occupations subject to licensing has been growing, the data available to investigate the incidence and effects of licensing have improved immeasurably, and the policy environment surrounding licensing has changed. This issue reflects these changes with eight papers from North America and Europe covering the incidence of licensing, and its effects on wages, inequality, employment, quality of service provision and rent extraction by the organizations who undertake licensing.